2022
DOI: 10.7759/cureus.21520
|View full text |Cite
|
Sign up to set email alerts
|

A National Cross-Sectional Study of the Characteristics, Strengths, and Challenges of College Students With Attention Deficit Hyperactivity Disorder

Abstract: Introduction: A substantial proportion of college students experience challenges transitioning from pediatrics to the adult healthcare system. Combined internal medicine and pediatrics (Med-Peds) providers are frequently tasked with facilitating this transition and promoting the health and well-being of this population. There is an increasing proportion of college students with Attention Deficit Hyperactivity Disorder (ADHD) in the U.S. This population experiences particularly pronounced challenges navigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021). Nine studies utilized self‐reported responses of autistic individuals (Fernandes et al, 2021; Hotez et al, 2022; McGhee Hassrick et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022; Song, Salzer, Nonnemacher, & Shea, 2022; Sosnowy et al, 2018; Sosnowy et al, 2019; Steinberg et al, 2022). Six articles included autistic co‐authors on the writing team (Lord et al, 2022; Roux et al, 2019; Roux, Rast, Anderson, et al, 2020; Roux, Rast, Garfield, et al, 2020; Shattuck et al, 2020; Steinberg et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021). Nine studies utilized self‐reported responses of autistic individuals (Fernandes et al, 2021; Hotez et al, 2022; McGhee Hassrick et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022; Song, Salzer, Nonnemacher, & Shea, 2022; Sosnowy et al, 2018; Sosnowy et al, 2019; Steinberg et al, 2022). Six articles included autistic co‐authors on the writing team (Lord et al, 2022; Roux et al, 2019; Roux, Rast, Anderson, et al, 2020; Roux, Rast, Garfield, et al, 2020; Shattuck et al, 2020; Steinberg et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Lower access to post‐secondary education supports was related to lower likelihood of employment following Vocational Rehabilitation services (Rast et al, 2020). Presence of mental and physical health issues was related to academic issues in postsecondary education (Fernandes et al, 2021; Hotez et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there is an increasing prevalence of ADHD among college students. The prevalence of ADHD was estimated to be 5.6% based on a nationally representative sample of first-year US college students (Hotez et al, 2022), while a cross-national WHO World Mental Health Survey reported that 18.8% of the US college freshmen in the sample screened positive for ADHD (Mak et al, 2022). The increasing enrollment of neurodivergent students in higher education underscores the necessity to understand and support their unique experiences and needs.…”
Section: Neurodivergent Students In Postsecondary Educationmentioning
confidence: 99%
“…Specifically, autistic college students face challenges such as anxiety, depression, loneliness, and marginalization (Anderson et al, 2017;Fernandes et al, 2021;Gelbar et al, 2014). Similarly, students with ADHD encounter difficulties with social relationships and adjustment to college life (Weyandt & DuPaul, 2008), and are more likely to report feelings of depression and being overwhelmed (Hotez et al, 2022).…”
Section: Neurodivergent Students In Postsecondary Educationmentioning
confidence: 99%
“…Specifically, autistic college students face challenges such as anxiety, depression, loneliness and marginalization (Anderson et al., 2017; Fernandes et al., 2021; Gelbar et al., 2014). Similarly, students with ADHD encounter difficulties with social relationships and adjustment to college life (Weyandt & DuPaul, 2008), and are more likely to report feelings of depression and being overwhelmed (Hotez et al., 2022). From parents' perspective, the perceived challenges for autistic college students include self‐advocacy, managing emotions and managing personal/adaptive skills, while the perceived challenges for students with ADHD are primarily attention and time management (Elias & White, 2018).…”
Section: Introductionmentioning
confidence: 99%